92.6k views
4 votes
37x+26=42x+6
someone please help me solve this step by step

User Roughnecks
by
5.2k points

2 Answers

0 votes

Answer:

x = 4

Explanation:

1. Subtract 26 on both equation. (37+26−26=42+6−26)

2. Simplify and Subtract the numbers and repeat. (37=42−20)

3. Subtract 42x on both equation. (37−42=42−20−42)

4. Put together (simplify). (−5=−20)

5. Now divided with -5x. ( −5/−5=−20/−5)

6. Get your answer! (=x4)

~~~Hope this helps~~~

User Alexander Klimenko
by
5.2k points
3 votes

Explanation:

37x+26=42x+6

x=4

If am wrong sorry

User Enjayem
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.